The effect of non-monotonicity of two-phase deformation processes on the limit of deformability of thin sheets - Devedžić, Branislav; Aleksandrović, Srbislav (Journal of Production Engineering, 1994)
The paper presents a parallel comparison of the limit deformability curves of thin sheets obtained using two theoretical approaches and an experimental procedure. Based on the theory of microstructure decohesion and the so called combined theoretical model, computer programs have been developed, making it relatively easy to obtain limit curves based on a few key material and deformation process characteristics.